Anthropometric and metabolic parameters associated with visceral fat in non-obese type 2 diabetes individuals - Ming Jiao; Jiaoli Chen; Xiaoling Wang; Wenyu Tao; Yunhua Feng; Huijun Yang; Haiying Yang; Shanshan Zhao; Ying Yang; Yiping Li (Diabetology & Metabolic Syndrome)
Abstract Background and Aim Visceral fat (VF) was proved to be a more precise predictor of atherosclerotic cardiovascular disease (ASCVD) risk in individuals with type 2 diabetes mellitus (T2DM) than body mass index (BMI) itself. Even when the BMI was normal, visceral fat area (VFA) ≥ 90 cm² could raise the ten-year risk of developing ASCVD. Therefore, it was worth evaluating the association of influencing factors with high VF in non-obese T2DM individuals. Methods This study enrolled 1,409 T2DM participants with T2DM, of whom 538 had a normal BMI. Based on VFA, these subjects were divided into two groups: VF (+) (VFA ≥ 90cm2) (n = 110) and VF (-) (VFA < 90cm2) (n = 428). The measurement of VFA was conducted using an Omron VF measuring device. Anthropometric and metabolic parameters were detected. Novel insulin resistance indices, such as lipid accumulation product (LAP) was calculated. Factors associated with VF were screened using univariate analysis, multifactorial binary logistic regression models and chi-squared automatic interaction detector decision tree model. Results The VF (+) OB (-) (BMI ≤ 23.9 kg/m2) prevalence were 7.8% in T2DM subjects (n = 1,409) and 20.4% in T2DM subjects with normal BMI (n = 538), respectively. In T2DM subjects with normal BMI, the logistic regression model suggested that neck circumference (NC) had an odds ratio (OR) of 1.891 (95% CI: 1.165–3.069, P = 0.010). The OR for VF gradually increased from the 1st to the 4th in LAP quartile (P < 0.05). LAP emerged as the root node, followed by NC in the decision tree model. Receiver operating characteristic curve (ROC) analysis demonstrated that the area under the curve (AUC) for NC in predicting high VF levels was 0.640 for males and 0.682 for females. Optimal NC cut-off points were 37.75 cm for males and 34.75 cm for females, respectively. Additionally, the AUC values of LAP in predicting high VF levels were 0.745 for males and 0.772 for females, with optimal LAP cut-off points of 22.64 and 26.45 for males and females, respectively. Conclusion This study identified NC and LAP can be considered predictors of high VF in T2DM subjects with normal BMI. Graphical Abstract